Desenvolvimento de um programa computacional para auxiliar o dimensionamento de trens de engrenagens cilíndricas retas - Esperança, João Marcos Salbego (2022)
In machine design, a common task of the mechanical engineer is the sizing of a system whose function is to modify and transmit torque and rotational speed from one machine to another. Spur gear trains are an example of this type of system, in which the designer aims to determine the gear shapes and arrangements that will produce the expected results. Currently, this process is highly standardized and has technical standards published by authorities on the subject, such as AGMA. However, although these standards provide guidelines for the gear sizing, this process is time-consuming for the designer, as it requires an indefinite number of repetitions and decisions. This is because the design calculations are performed based on some presupposed parameters that, at some point, may prove to be inadequate and force the designer to go back in the process, stipulating new values. Seeking to solve this challenge, this work aims to develop a computer program that automates the sizing and specifying process of a spur gear train. The program code, named DATERA, was written using the MATLAB programming language and its operating algorithm was elaborated based on the methods published by AGMA presented in reference literature, such as the works of Norton (2013), Shigley, Mischke and Budynas (2005), Juvinall and Marshek (2013), and Shiguemoto and Olivio (2019). To verify the effectiveness of DATERA, a gear train design was proposed, whose initial premises and parameters were inserted in the program and also used to perform the sizing through analytical calculations. Then, the results generated by the two methods were compared and it was proved that the program indeed produces values consistent with the analytical calculations, but in a much faster and more practical way.